Voltage Regulation in a Microgid with Hybrid PV/Wind Energy - Joseph Olawole Petinrin; Mohamed Shaaban; J.O. Agbolade (Institute of Advanced Engineering and Science, 2015)
Autonomous operation of a microgrid system hinges on the efficient combination of various energy resources to maintain self-sustainability of energy supply. Furthermore, it is equally important to coordinate the resources to regulate the microgrid voltage profile. The problem becomes more complicated if these resources have intermittent characteristics such as solar PV and wind turbines. The potential for using energy storage promise to have a major impact on schemes for voltage control in a microgrid. A hybrid Particle Swarm Optimization/Gravitational Search Algorithm (PSOGSA) based approach is used in this paper to contemplate the optimum size and location of energy storage to reduce voltage variations and feeder losses caused by PV/wind energy integrated in a microgrid. Effectiveness of the proposed method is implemented through a quasi-static time sequence analysis over a 24-hourly simulation period on autonomous Microgrid system. The corresponding voltage profile is analyzed under different operating conditions, with high penetration level of PV/wind energy. Test results show that the energy storage causes reduction in system losses and enhances system capability to maintain voltages within the permissible limits. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7905